Multi-omics analysis of molecular mechanisms driving the grafting- enhanced resistance of tea plants to Colletotrichum camelliae - Li, Yue-Xin; Lin, Kai-Qin; Wang, An-Ran; Wei, Jie; Yan, Dong-Hai; Zhao, De-Gang (Frontiers in Plant Science, 2026)
BackgroundThe fungal pathogen Colletotrichum camelliae causes a devastating disease that severely limits tea plant (Camellia sinensis) yield and quality. Grafting onto resistant rootstocks offers a sustainable control strategy, yet resistant rootstocks confer scion protection remains obscure.MethodsSusceptible cultivar ‘Qianmei 818’ was grafted onto resistant ‘Qianmei 419’. Profiled systemic defenses using integrated RNA-seq, sRNA-seq, and metabolomics, complemented by phytohormone and defense-enzyme assays and qRT-PCR validation.ResultsHetero-grafting conferred near-complete resistance, reducing lesion diameters by 98.71% compared to ungrafted controls, with elevated PAL activity and accumulation of IAA, GA3, and MeSA. Multi-omics analyses identified 1205 differentially expressed genes, 157 differentially expressed miRNAs, and 791 differential metabolites. Pathway integration indicated extensive reprogramming of phenylpropanoid biosynthesis, sulfur metabolism, and plant hormone signaling. Notably, specific miRNA-mRNA regulatory modules, such as downregulation of csi-miR395b-3p and a novel miR397 paralleled up-regulation of their targets in sulfur assimilation (CsAPS1) and lignin biosynthesis (CsCCoAOMT, CsCCR2), respectively, linking miRNA control to reinforcement of structural and biochemical defenses.ConclusionsResistant rootstocks activate scion-wide defense networks through miRNA-mediated transcriptome-metabolome remodeling, achieving robust resistance while maintaining tea quality. The elucidated modules provide actionable targets and genetic resources for breeding and grafting strategies toward sustainable disease management.